LncRNA DANCR promotes the migration an invasion and of trophoblast cells through microRNA-214-5p in preeclampsia. Issue 2 (20th December 2021) - Zhang, Qian; Wang, Zhenzhen; Cheng, Xianghong; Wu, Haiying
ABSTRACT: Studies have shown that lncRNA DANCR is down-regulated in placental tissues of patients with preeclampsia (PE). The aim of this study was to explore the effect of lncRNA DANCR on trophoblast cells as well as its acting mechanism. We disrupted or overexpressed lncRNA DANCR in trophoblast cells HTR-8/SVneo and JEG-3 and detected the associated cellular functional changes by MTT, flow cytometry, Transwell experiment, and scratch experiment. The results showed that overexpression of lncRNA DANCR significantly increased the proliferation, invasion, migration, and EMT process of trophoblast cells. Interfering with lncRNA DANCR showed the opposite result. Further, the targeted interaction between lncRNA DANCR and miR-214-5p was confirmed by the dual-luciferase reporter gene assay. In addition, the expression of PI3K/AKT signaling pathway-related proteins was analyzed by Western blot. Overexpression of lncRNA DANCR can increase the phosphorylation of PI3K/AKT protein and activate this signaling pathway. In conclusion, the enforcing of lncRNA DANCR activates the activation of the PI3K/AKT pathway by down-regulating miR-214-5p, and promotes the migration and invasion of chorionic trophoblast cells. This provides a potential new target for PE therapy.